Evaluasi Kurikulum Pendidikan Islam Berbasis Pesantren dalam Meningkatkan Kompetensi Spiritual dan Sosial Santri (Studi Kasus di Asrama 10 Hurun Inn Pondok Pesantren Darul Ulum Jombang) - Ainun Nikmah Rohmatul Ilmi (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to evaluate the *pesantren*-based Islamic education curriculum regarding its role in enhancing the spiritual and social competencies of *santri* (students) at Dormitory 10 Hurun Inn, Darul Ulum Islamic Boarding School, Jombang. The study is motivated by the need for an evaluation system capable of objectively measuring the curriculum's success, given that character formation has historically relied on habituation and role modeling without the support of standardized evaluation instruments. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, participant observation, and document analysis, and subsequently analyzed using the interactive model developed by Miles, Huberman, and Saldaña. Data validity was ensured through source triangulation, technique triangulation, member checking, and an audit trail. The findings reveal that the Islamic education curriculum at Dormitory 10 Hurun Inn operates as a "living curriculum," manifested through acts of worship, habituation, role modeling, and the students' communal life. While the curriculum effectively shapes spiritual and social behaviors, it lacks formally documented objectives, clear achievement indicators, and systematic evaluation instruments. The development of spiritual and social competencies is more pronounced in the behavioral aspect (moral action) than in the internal awareness aspect (moral feeling). Therefore, this study recommends integrating the traditional strengths of the *pesantren* with the Responsive Evaluation model to create an evaluation system that is more structured and objective while preserving the distinctive characteristics of *pesantren* education